(untitled) (World Science, 2020)
The magnitudes of the kinematic parameters of projectiles motion in the air depends on deterministic (form of projectile, its mass, temperature of air and charge, atmospheric pressure, derivation) and nondeterministic (muzzle velocity, magnitude and direction of wind velocity) values. During the projectile movement, its weight and frontal air resistance force have a determining influence on its dynamics. In the article it is investigated proposed by authors the mathematical model of determination of the functional dependence of the magnitude of the frontal air resistance force of the projectile’s motion on its velocity, mass and caliber, geometric characteristics, temperature and density of air, atmospheric pressure, sound speed in air. Since the trajectory of movement of the BM1 projectile released from the T-12 (MT-12) is canopy, it is assumed that during the projectile’s flight the air temperature and atmospheric pressure are unchanged and equal to their value at the point of the gun.